Social Media Use and Acculturation among International Students in Xi'an: A Pilot Study Based on the Uses and Gratifications Framework - Zhu, 93daijun0827 (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
With the growing internationalization of Chinese higher education, the cultural adaptation of international students has become an increasingly relevant topic. Social media plays a vital role in their daily lives, facilitating information access, social interaction, and emotional support. Grounded in the Uses and Gratifications (U&G) framework and acculturation theory, this pilot study conducts a descriptive statistical analysis (n = 40) of international students in Xi'an, focusing on their motivations for social media use, intergroup contact, perceived social support, and acculturation outcomes. Results indicate that students tend to use social media in a strategic and instrumental manner, primarily to access localized information and connect with peers. While online cross-cultural interaction is relatively frequent, a sense of belonging remains limited. Social media proves effective for informational support but less so for emotional reassurance or practical intervention. Furthermore, findings suggest a Behavioural–psychological adaptation gap, where surface-level adjustment precedes deeper cultural integration. The study highlights the selective role of social media in the acculturation process and calls for more comprehensive, emotionally responsive support systems in higher education institutions.